Case Report: Use of submental artery perforator flap for reconstructing defects following sinonasal tumor resection - Li, Minghong; Zhao, Ning; Jiang, Feifei; Tan, Xuexin; Lu, Li; Yan, Aihui (Frontiers in Oncology, 2025)
BackgroundSinonasal malignancies (SNMs) invading orbital and maxillofacial structures require complex reconstructive techniques. The submental artery perforator flap (SMAPF) provides a promising reconstructive option due to its vascular reliability and adaptability.MethodsA retrospective study reviewed three patients treated between December 2021 and November 2022 with radical resection of sinonasal malignancies, including orbital content removal. All patients underwent immediate reconstruction using an extended-pedicle SMAPF. The flap pedicle was elongated via microsurgical dissection under 2.5× magnification. Postoperative evaluations were conducted at 1, 3, and 6 months using nasal endoscopy and CT imaging.ResultsAll flaps survived without vascular compromise. No local recurrence or distant metastasis was observed. Functional and aesthetic outcomes were favorable, with no major complications reported.ConclusionsThe extended pedicled SMAPF is a reliable and effective option for one-stage reconstruction of complex orbital and maxillofacial defects following sinonasal malignancy resection. It provides stable vascular support, and functional and aesthetic outcomes meet clinical expectations.